The Effect of Compound Exercises on Some Fundamental Skills in Youth Soccer Goalkeepers - saddam, hussein; Malek, Faris (Journal of Physical Education, 2023)
The research aimed at deigning compound exercises for developing some fundamental skills for youth soccer players as well as identifying the effect of these exercises on the development of fundamental skills in youth soccer goalkeepers. The researchers used the experimental method on (4) youth goalkeepers from clubs participating in Salah Al Deen League for youth 2021 – 2022. The training program consisted of (8) weeks training with 24 training session using CrossFit style with training stations that include an exercise. Goalkeepers should perform each exercise within a specific time without a rest moving to the next station. The researchers used heart pulse as indicator of training intensity. The data was collected and treated using SPSS to conclude that the subjects developed significantly in fundamental skills understudy. The compound exercises and their arrangement had a positive effect in developing these skills in subjects understudy. Finally, the researchers recommended generalizing these exercises using cross fit style on all sport clubs to train youth players during special preparation phase.